2015
DOI: 10.1097/nur.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

The Headache Electronic Diary for Children With Concussion

Abstract: The new HED-CC provides for thorough assessment and documentation of postconcussion headache. Proactive, real-time measurement helps children remember the details of their headache pain and correlating events/circumstances. An appealing, age-appropriate measure increases the likelihood of children's symptom tracking and data accuracy. The HED-CC will improve clinicians' understanding of postconcussion headache and guide treatment. Additional testing with a larger sample is required to establish clinical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…All the adolescents in this study experienced a headache, commonly known as the most prevalent symptom after concussion (Blume, ; Eisenberg, Meehan, & Mannix, ). In agreement with previous research, there are many descriptions of headache (Pasek et al, ). Without being prompted, these adolescents shared the unique characteristics of their headaches.…”
Section: Discussionsupporting
confidence: 92%
“…All the adolescents in this study experienced a headache, commonly known as the most prevalent symptom after concussion (Blume, ; Eisenberg, Meehan, & Mannix, ). In agreement with previous research, there are many descriptions of headache (Pasek et al, ). Without being prompted, these adolescents shared the unique characteristics of their headaches.…”
Section: Discussionsupporting
confidence: 92%
“…56,57 Although there is a paucity of literature specifically Our study demonstrated the willingness of families to respond to an electronic follow-up questionnaire. This is consistent with previous studies using a similar follow-up strategy for concussed children, 7,59,60 Using this strategy has many advantages including the option for children to answer the questionnaire when they desire, the immediate transfer of data to a database, and inherent cost savings. However, it may be associated with limitations related to the absence of supervision by a professional to ensure that responses are appropriate.…”
Section: Discussionsupporting
confidence: 76%
“…Patient diaries have been used in various neurological fields, including headache (Russell et al , 1992, 1994; Allena et al , 2012; Seidel et al , 2012; Stinson et al , 2013; Larsson and Fichtel, 2014; Barmettler et al , 2015; Heyer and Rose, 2015; Pasek et al , 2015), epilepsy (Le et al , 2011; Haut et al , 2013; Cobabe et al , 2015; Fisher et al , 2015), sleep, other pain, etc. (Le et al , 2011; Jacob et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Le et al , 2011; Jacob et al , 2012). Several of these have been in the form of electronic diaries (Haut et al , 2013; Stinson et al , 2013; Barmettler et al , 2015; Pasek et al , 2015), including on-line (Fisher et al , 2015), web-based (Le et al , 2011) through the internet (Heyer and Rose, 2015), on-palm device (Allena et al , 2012), and smartphone (Jacob et al , 2012). …”
Section: Introductionmentioning
confidence: 99%